EVALUASI PROGRAM TENAGA HARIAN LEPAS TENAGA BANTU PENYULUH PERTANIAN (SEBUAH PENELITIAN DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2007) (EVALUATION ON THE CONTRACT-BASED AGRICULTURE EXTENSION WORKERS PROGRAM - A RESEARCH IN D.I. YOGYAKARTA PROVINCE IN - Yulianto, Gunawan; Redono, Cucuk; Agus, Fransiskus Xaverius; Kurniawan, Joni (Jurnal Ilmu-Ilmu Pertanian, 2008)
This research aims to evaluate the achievements of the Contract-based Agriculture Extension Workers Program (Program THL TBPP) in D.I. Yogyakarta Province, regarding the programs relevance to the presents needs, the participants characteristics, the quality of the introductory training implementation, the participants role at their respective placement locations, as well as BPP directors and farmer groups perceptions towards the extension workers. The approach in this research uses the CIPP (contex, input, process, product) model by Stufflebeam. The subject includes all 74 program participants, 74 board members of farmer group, and 20 BPP directors. The descriptive quantitative data analysis is done with SPSS 16.00 for Windows. This research reveals that the program is relevant to the need for agriculture extension services, the participantscharacteristics varies in the term of experience and educational background, accordingly introductory training and placement should be taken into consideration. The participantsmotivation at the work is relatively good. The quality of introductory training is relatively good, but need improvement in several aspects. BPP directors and farmer groups perceptions of the extension workers in performing their task are relatively good.